Trends in the European financial system and implications for supervision - Schoenmaker, Dirk (Henry Stewart Talks, 2009)
Challenges of European financial integration, Evidence on emerging pan-European financial institutions in Europe, Discussion of corporate and legal structures of financial institutions, Policy challenge of European financial institutions and national supervisors, Suggestion to establish a European system of financial supervisors